2013
DOI: 10.1371/journal.pone.0066391
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol Decrease IL-1β and TNF-α, Inhibits MMP-2, MMP-9, COX-2, and RANKL Expression, and Up-Regulates OPG in a Rat Model of Periodontitis

Abstract: Periodontal diseases are initiated primarily by Gram-negative, tooth-associated microbial biofilms that elicit a host response that causes osseous and soft tissue destruction. Carvedilol is a β-blocker used as a multifunctional neurohormonal antagonist that has been shown to act not only as an anti-oxidant but also as an anti-inflammatory drug. This study evaluated whether Carvedilol exerted a protective role against ligature-induced periodontitis in a rat model and defined how Carvedilol affected metalloprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 24 publications
(24 reference statements)
6
32
0
Order By: Relevance
“…Therefore, it could be suggested that the elimination of chronic inflammation related to active inflammation processes taking place in the periodontium, might lead to further benefits in the form of improved endothelial function of blood vessels. The subject of this pilot study was to examine the reduction of chronic inflammation related to PD influence on the clinical course and prognosis of CHF, based on the assessment of plasma concentrations of the inflammatory and neurohormonal markers NT-proBNP and TNF-a [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it could be suggested that the elimination of chronic inflammation related to active inflammation processes taking place in the periodontium, might lead to further benefits in the form of improved endothelial function of blood vessels. The subject of this pilot study was to examine the reduction of chronic inflammation related to PD influence on the clinical course and prognosis of CHF, based on the assessment of plasma concentrations of the inflammatory and neurohormonal markers NT-proBNP and TNF-a [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…MMP-3 has been implicated in joint and soft tissue destruction associated with these conditions, where it participates in the inflammatory response (10)(11)(12)(13). Synthesis of MMP-3 is tightly controlled in vivo (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…MMP-3 has been implicated in the joint and soft-tissue destruction associated with these conditions, where it participates in the inflammatory response (10)(11)(12)(13)(14). MMP-3 synthesis is tightly controlled in vivo (13,15).…”
Section: Introductionmentioning
confidence: 99%